Early inflammation–associated factors blunt sterol regulatory element‐binding proteins‐1‐mediated lipogenesis in high‐fat diet‐fed APPSWE/PSEN1dE9 mouse model of Alzheimer's disease. Issue 4 (10th December 2015) - Tang, Ying; Peng, Yunhua; Liu, Jing; Shi, Le; Wang, Yongyao; Long, Jiangang; Liu, Jiankang
Abstract: Alzheimer's disease (AD) patients have an increased incidence of Type 2 diabetes (T2D); however, the underlying mechanisms are not well understood. Since AD is considered a multifactorial disease that affects both the central nerves system and periphery and the dysregulation of hepatic lipid and glucose metabolism play critical roles in T2D, we, therefore, aim to explore the influence of AD genotype on the liver during the progress of high‐fat diet (HFD)‐induced T2D. Fourteen‐week‐old female APP SWE /PSEN1dE9 (AD) mice and age‐, gender‐matched wild‐type controls C57BL/6J (WT) mice were fed a HFD (45% kcal fat content) or a standard chow diet (chow, 12% kcal fat content) for 22 weeks. The effects of diet and genotype were analyzed. Mouse primary hepatocytes were used to decipher the underlying mechanisms. HFD induced significantly higher body weight gain, more severe hyperglycemia, glucose intolerance and hepatic insulin resistance in AD mice than in WT mice. However, AD mice showed reduced HFD‐induced hepatic steatosis, and SREBP‐1‐mediated lipogenic signaling was activated by HFD in WT mice but not in AD mice. In addition, 14‐week‐old AD mice exhibited higher expression of NF‐κB p65, p‐JNK and p‐p38MAPK, as well as higher hepatic and serum contents of IL‐6 and TNFα. In mouse primary hepatocyte cultures, IL‐6 and TNFα inhibited high‐glucose plus insulin‐induced activation of SREBP‐1‐mediated lipogenic signaling and biosynthesis of non‐esterified fatty acid and triglyceride. Early inflammation–associated factors most likely diminish HFD‐induced hepatic lipid deposition by inhibiting SREBP‐1‐mediated de novo lipogenesis, thus driving substrate flux to glucose production for hyperglycemia and hepatic insulin resistance in T2D development. Alzheimer's disease (AD) is a multifactorial disease affecting both central nerves system and periphery organs. Therefore, we explored the hepatic susceptibility to high‐fat diet (HFD) in AD mice. We found that AD mice were resistant to HFD‐induced hepatic fat accumulation in spite of more severe obesity, hyperglycemia, glucose intolerance and hepatic insulin resistance. Mechanistically, AD mice exhibited hepatic inflammation at an early stage, which inhibited sterol regulatory element‐binding proteins‐1 (SREBP‐1)‐mediated de novo lipogenesis, and most likely drive substrate flux to glucose production for hyperglycemia and hepatic insulin resistance. Cover Image for this issue: doi:10.1111/jnc.13306 . Abstract : Alzheimer's disease (AD) is a multifactorial disease affecting both central nerves system and periphery organs. Therefore, we explored the hepatic susceptibility to high‐fat diet (HFD) in AD mice. We found that AD mice were resistant to HFD‐induced hepatic fat accumulation in spite of more severe obesity, hyperglycemia, glucose intolerance and hepatic insulin resistance. Mechanistically, AD mice exhibited hepatic inflammation at an early stage, which inhibited sterol regulatory element‐binding proteins‐1 (SREBP‐1)‐mediated de novo lipogenesis, and most likely drive substrate flux to glucose production for hyperglycemia and hepatic insulin resistance. Cover Image for this issue: doi:10.1111/jnc.13306 .